IMPROVEMENT OF TECHNICAL AND TACTICAL TRAINING OF YOUNG TABLE TENNIS PLAYERS IN FOREIGN PRACTICE - Wang Xiangyu,; Ryzhkova L.G. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify areas for improving the technical and tactical training of young table tennis players in foreign practice. Methods and structure of the study. In the course of the study, an analysis of foreign scientific theoretical, methodological literature on the issues of sports training in table tennis was carried out. Results and conclusions. It was revealed that among the modern foreign trends aimed at improving technical and tactical skills, the following stand out: the development of perceptual-motor skills, and the possibility of their predictive value for future results, the formation, improvement and development of skills using the VR environment, as well as psychological support in the form of mindfulness training.